Race and racism in Russia - Zacharov, Nikolaj Valerʹevič 1978- (Palgrave Macmillan, 2015)
"Since the 1990s, there have been striking changes in racial ideas, practices, exclusions and violence in Russia. By showing how the processes of globalization and racialization are interrelated, Zakharov seeks to demonstrate and explore the roles these play in Russia's new nationhood project. The book employs a new threefold theoretical elaboration of racialization, examining the process in terms of 'making', 'doing', and finally 'becoming'. These three elements are considered through discussions of a wide variety of aspects of Russian identity and nationalism, from the analysis of subcultures to explorations of nation-building. Race and Racism in Russia provides important new theories and substantive insights into race and ethnicity in a Russian context, and will be a valuable resource for scholars of Postcolonial Studies, Social Theory and Race"--
Includes bibliographical references and index
1. Global Racisms and Racism in Russia : An Introduction -- 2. Race and Racism in the Russian Past -- 3. Race, Racialization, and Racism : A New Theoretical Framework -- 4. Making Race in the Russian Academia -- 5. Rioting for Whiteness : Doing Race on the Squares of Moscow -- 6. Becoming Racial : Race As a New Form of Inequality -- 7. Geopolitics of Racism and the Nation-Building Processes -- 8. Concluding Discussion
Keywords: Geschichte; Racism / Russia (Federation); Globalization / Social aspects / Russia (Federation); Nationalism / Russia (Federation); SOCIAL SCIENCE / Emigration & Immigration; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Minority Studies; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Violence in Society; Ethnic relations; Globalization / Social aspects; Nationalism; Political science; Race relations; Racism; Gesellschaft; Globalisierung; Nationalismus; Politik; Politische Wissenschaft; Rassismus; Ethnische Identität; Russia (Federation) / Race relations; Russia (Federation) / Ethnic relations; Russia (Federation) / Politics and government / 1991-; Russia (Federation); Russland